The position of the Algerians on colonial policy - Attabi, Djamel; Lounici, Brahim (Journal of Social Sciences and Humanities, 2021)
Endowments have a social, economic, and scientific importance in the community that Muslims have created to respect money and housing, and to help scholars, students, the poor, strangers, refugees, and institutions maintenance. The status of the endowments did not continue unchanged, that by occupying Algeria in 1830, the French colonial administration began to investigate the various conditions that prevailed, and to search for means that would complete control over the entire Algerian country, in order to establish a clear administrative and regional base, since the colonial administration began from the beginning Following the settlement policy, she recruited her all the financial and human capabilities, military and civilian. It issued a set of laws, decrees and interim decrees to seize and confiscate these properties. It started from the decree of September 08, 1830, through which he wanted to obliterate the features of the Islamic identity of this country and had a firm stance towards religious institutions, including endowments, the judiciary, and property of worship, so he undermined them and demolished their landmarks as a barrier to Tosha And for the French people of Algeria, the autonomy of religious institutions disturbed the French authority, and it did not give its hand for expansion and control, and in order for it to gain control, the endowment resources must be ended, so that the mosque, the school, and the Sharia court become tools in the hands of the Ada Colonial times, to include the endowment institutions within the ownership of the state treasury (the domain). Thus, the first blow struck by French colonialism in Algeria was after the elimination of the foundations of the Algerian state, that the Islamic endowments were attached to the interest of the properties of the French state (the Domine), and it became the authority to run the endowment administration by the French administration, which opened the way for the French authorities to dispose of them according to French laws, And the possibility of the transfer of endowments to the possession of French settlers in violation of the provisions of Islamic Sharia, which does not allow the transfer of ownership or sale, the most important French figures who fought the Islamic endowments of both General Clozel and General Pogo, in encouragement of the policy of Alas Ammar the settlement in Algeria, and the intolerance of the Christian religion and their hatred of the Crusader against Islam and Muslims. Thus, the French authorities seized the endowment properties belonging to the Algerian Muslim community, striking at the wall the legitimacy of the endowment and its binding legal form, and respecting its conditions, which led to the retreat of real estate properties belonging to Islamic endowments inside the cities And in the countryside. The Algerian reactions were strong, headed by the clergy, scholars, and notables, with the facilitation of the means of resistance, for the most ferocious Christian barbarism, and the repressive measures practiced by the occupation authorities towards them did not prevent them from carrying out their role and mission, and did not lead them to negativity and surrender but rather led them to stand firmly and persistently French colonialism and its practice and exhausted all possible ways to make their voices heard. These solemn acts came to confirm that this people did not surrender and remained fighting with all their modest capabilities. Among the protesters were the clergy and scholars, Ibn al-Annabi, Ibn al-Kababti, HamdanKhoja and Boudaraba, if The confiscation of endowments had negative repercussions on all aspects of religious, cultural, economic and social life, and its negative repercussions are manifested on the religious side in Algeria, by the French authorities fighting the Islamic religion by eliminating the role of the endowments in preserving Islamic rituals and restricting Muslim clerics and scholars. The interpretation of the French colonialism in Algeria resorting to this policy against Islamic endowments as a kind of religious fanaticism, in addition to feeling superiority and denial of Islamic.